Preparation method of flexible two-dimensional zinc-based complex and low-carbon hydrocarbon separation application of flexible two-dimensional zinc-based complex

By adopting a pillared ligand tailoring strategy to synthesize flexible two-dimensional zinc-based complexes, the technical problem of the lack of flexible two-dimensional MOF design in the existing technology has been solved, and efficient adsorption and separation effects in the field of low-carbon hydrocarbon gas separation have been achieved.

CN119350647AActive Publication Date: 2025-01-24CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411495437.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing technology lacks cases of using column ligand cutting strategies to design and synthesize flexible two-dimensional MOFs, which limits the application of flexible MOFs in the fields of binary and triple gas separation.

Method used

A zinc-based complex was synthesized using a pillared ligand tailoring strategy. The general chemical formula is [Zn3(TMTA)2(DPP)·DMF·H2O]. This complex has a flexible two-dimensional structure and is suitable for the separation of low carbon hydrocarbons.

Benefits of technology

The zinc-based complex shows good adsorption performance and separation selectivity in the field of low-carbon hydrocarbon gas separation, and can effectively separate gases such as CO2, C2H2, C2H4, and C2H6, expanding the application potential of flexible MOF in the field of gas separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350647A_ABST
    Figure CN119350647A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new materials, and particularly relates to a zinc-based complex as well as a preparation method and application thereof. The chemical general formula is [Zn3 (TMTA) 3 (DPP). DMF.H2O], Zn is a divalent zinc ion, TMTA is a deprotonated 4, 4 ', 4' '-(2, 4, 6-trimethylbenzene-1, 3, 5) tribenzoic acid ligand, DPP is a 4-(2, 5-difluoro-4-bromophenyl) pyridine ligand, DMF.H2O is a 4-(2, 5-difluoro-4-bromophenyl) pyridine ligand, DMF.H2O is a 4-(2, 5-difluoro-1, 3, 5-triphenyl-1, 3, 5-triphenyl-1, 3, 5-triphenyl-1, 3, 5-triphenyl-1, 3, 5-triphenyl-1, 3, 5-triphenyl-1, wherein the structure of the zinc-based complex belongs to a triclinic system and a P-1 space group, and the unit cell parameters of the zinc-based complex are as follows: the axial length is # imgabs 0 # # imgabs 1 #, the axial angle alpha is equal to 60.225 (9) degrees, the beta is equal to 73.437 (8) degrees, the gamma is equal to 84.579 (7) degrees, and the unit cell volume is # imgabs 2 # Z is equal to 2. The zinc-based complex can be used for preparing an adsorption material, an antibacterial material, a catalytic material, a photoelectromagnetic material and a drug carrier material, belongs to a metal-organic framework structure, and is a composite functional porous material with great potential. The zinc-based complex can be applied to the field of low-carbon hydrocarbon gas separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and specifically relates to a preparation method of a flexible two-dimensional zinc-based complex and its application in the separation of low-carbon hydrocarbons. Background Art

[0002] Nanostructured materials, due to their structural characteristics, show excellent performance in many aspects. In the past two decades, a class of organic-inorganic hybrid nanoporous materials called "metal-organic framework (MOF)" has received widespread attention and has become one of the research hotspots and frontiers in the field of new materials. MOF materials have attracted widespread attention due to their unique and excellent performance and have been applied in materials, chemistry and other fields. Nowadays, in terms of material synthesis, there is also a shift from finding new structures to application-oriented precision synthesis. MOF materials have become a new generation of functional materials after zeolites, activated carbon, etc. There are two main ways to prepare functional MOF materials. One is to anchor the functional groups to the framework through post-modification to give it specific functionality; the other is to directly prepare functional framework materials by pre-designing and synthesizing functional building unit ligands. This bottom-up pre-modification method can make the target functional groups accurately distributed on the framework of the material, which is conducive to controlling the position and number of active sites, and effectively avoiding the destruction of the material structure and porosity by modifying the functional groups on the framework.

[0003] Compared with porous adsorbents such as molecular sieves and activated carbon, MOF materials have unique advantages in the field of gas adsorption and separation due to their tailorable frameworks and rich and diverse pores. Adsorption is an exothermic process, and rigid pore structures make it difficult to dissipate the binding energy generated by the adsorption process, thereby increasing the adsorption capacity. Flexible MOFs that undergo structural transformations caused by changes in the guest, pressure, or temperature are more likely to undergo structural changes to offset this energy, thus having great potential in challenging separation processes. Therefore, flexible pore structures are expected to become the preferred material for separating and purifying olefins in binary or even multi-component mixtures.

[0004] So far, designing flexible MOFs for binary and ternary gas separation has great application prospects. In recent years, many literatures have reported the synthesis methods of flexible MOFs and their applications in gas separation. For example, Qiubing Dong, Xin Zhang, Shuang Liu, Angew. Chem. Int. Ed. 2020, 59, pp 22756-22762 used 1,4-di(1H-imidazole-1-yl)benzene and Cu(SiF6)·6H2O to construct NTU-65. At a specific temperature, NTU-65 can adsorb a large amount of C2H2 and CO2, while the adsorption of C2H4 is negligible, thereby achieving one-step purification of C2H4; 2021, Mohana Shivanna, Ken-ichi Otake, Bai-Qiao Song, Angew. Chem. Int. Ed. 2021, 6, pp 20383-20390 selected 1,2-bis(4-pyridyl)ethane and ZnSiF6 2- It exhibits a sharp adsorption capacity for C2H2 at low pressure and can selectively separate C2H4 / CO2 / C2H2. Lingyao Wang, Nuo Xu, Yongqi Hu, Nano Res. 2023, 16, pp 3536–3541 ZNU-5 was synthesized from 1,4-di(1H-imidazole-1-yl)benzene, (NH4)2TiF6 and Cu(NO3)2·3H2O. ZNU-5 has a high C2H2 adsorption capacity and has good C2H2 / CO2, C2H2 / C2H4 and C2H2 / CH4 separation selectivity at room temperature.

[0005] The strategies used to construct the flexible complexes mentioned above all come from the twisting of the ligands, and there has never been a case reported of using the pillared ligand tailoring strategy to design and synthesize flexible two-dimensional MOFs. In other words, there is a lack of a flexible two-dimensional complex synthesized using the pillared ligand tailoring strategy. Summary of the invention

[0006] In order to solve the technical problems in the above-mentioned background technology, the present invention provides a method for synthesizing a flexible two-dimensional zinc-based complex by using a tailoring strategy of a pillared ligand.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a zinc-based complex, the general chemical formula of which is [Zn3(TMTA)2(DPP)·DMF·H2O], wherein Zn is a divalent zinc ion, TMTA is a deprotonated 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, and DPP is a 4-(2,5-difluoro-4-bromophenyl)pyridine ligand;

[0008] The structure of the zinc-based complex belongs to the triclinic system, the P-1 space group, and its unit cell parameter is the axis length. Axis angle α=60.225(9)°, β=73.437(8)°, γ=84.579(7)°, Z=2.

[0009] The beneficial effects of the present invention are: the zinc-based complex of the present invention can be used to prepare adsorption materials, antibacterial materials, catalytic materials, opto-electromagnetic materials and drug carrier materials. The zinc-based complex of the invention belongs to a metal-organic framework structure and is a composite functional porous material with great potential. The zinc-based complex crystal of the present invention is tested under 293K conditions using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data is received on the EosCCD. A graphite monochromator is used, and λ(CuKα) is Data analysis was performed using the CrysAlisPro tool with a variable speed arbitrary angle scan mode from ω to 2θ, and absorption correction was performed. All structures were solved directly using the SHELXS program packaged in SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were treated anisotropically, and the hydrogen atoms of the organic ligands were generated by geometric symmetry (CH The structure of the zinc-based complex of the present invention belongs to the triclinic system, the P-1 space group, and the basic structural unit of the crystal is obtained by symmetric operation of the asymmetric unit. The symmetric operation code is 1 +X,+Y,-1+Z; 2 +X,-1+Y,+Z; 3 +X,1+Y,+Z; 4 +X,+Y,1+Z.

[0010] The asymmetric unit consists of a deprotonated ligand TMTA, a ligand DPP, three zinc ions and a coordinated water molecule.

[0011] The zinc ion is connected to four atoms in a four-coordinate mode. The four atoms connected to Zn1 are oxygen atoms (O2) from four carboxylates (O2-C1-O2) from three different ligands, and one is from an oxygen atom (O1) on a water molecule; the four atoms connected to Zn2 are oxygen atoms (O2) from four carboxylates (O2-C1-O2) from three different ligands, and one is from a nitrogen atom (N1) on the DPP ligand; the carboxylates (O2-C1-O2) in the ligand adopt a bidentate bridging mode to connect adjacent Zn ions, ultimately forming a binuclear [Zn3(TMTA)2(DPP)·DMF·H2O] structure. The structure of the zinc-based complex belongs to the triclinic system, P-1 space group, and its unit cell parameter is the axis length. Its unit cell parameter is the axis length Axis angle α=60.225(9)°, β=73.437(8)°, γ=84.579(7)°, Z=2.

[0012] The present invention also provides a method for preparing a zinc-based complex, comprising the following steps:

[0013] A. Dissolve 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine and zinc nitrate hexahydrate is 1:20:12.8, and the concentrations of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand and the 4-(2,5-difluoro-4-bromophenyl)pyridine ligand in the solution are 0.0054 mmol / L and 0.064 mmol / L, respectively.

[0014] B. Place the mixed solution in step A in a glass bottle and keep it warm at 90° C. for 24 to 48 hours to obtain the zinc-based complex.

[0015] The beneficial effects of the present invention are: the preparation method has simple conditions, the reaction can be carried out quickly, energy is saved, and time is saved. In addition, the preparation method of the zinc-based complex of the present invention has high yield, small amount of ligand used, and cost saving.

[0016] Based on the above technical solution, the present invention can also be improved as follows.

[0017] Furthermore, the solvent consists of N,N-dimethylformamide, ethanol and water, and the volume ratio of N,N-dimethylformamide, ethanol and water is 5:2:1.

[0018] The beneficial effect of adopting the above further scheme is that the solvent composed of N,N-dimethylformamide, ethanol and water is easy to obtain, low in price and less polluting.

[0019] Furthermore, the molar ratio of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine ligand and the zinc nitrate hexahydrate is 0.054:1.1:0.64, and the concentrations of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand and 4-(2,5-difluoro-4-bromophenyl)pyridine ligand in the solution are 0.0054 mmol / L and 0.064 mmol / L, respectively.

[0020] The beneficial effect of adopting the above further scheme is that the zinc-based complex obtained by the determined concentration and molar dosage ratio has better quality and the reaction is smoother.

[0021] The present invention also provides an application of a zinc-based complex in the field of low-carbon hydrocarbon gas separation. The zinc-based complex is subjected to an adsorption test on low-carbon hydrocarbons composed of CO2, C2H2, C2H4 and C2H6 to obtain differentiated adsorption amounts for adsorption separation.

[0022] The beneficial effect of the present invention is that the zinc-based complex is applied to the field of low-carbon hydrocarbon gas separation, making the function of the zinc-based flexible complex more comprehensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a structural diagram of an asymmetric structural unit of the zinc-based complex of the present invention;

[0024] Figure 2 is a structural diagram of the zinc-based complex of the present invention;

[0025] Figure 3 The thermogravimetric curve of the zinc-based complex of the present invention is shown in FIG. 1 , wherein the abscissa is the temperature and the ordinate is the weight loss percentage;

[0026] Figure 4 is the infrared spectrum of the zinc-based complex of the present invention, the abscissa is the wave number, and the ordinate is the transmittance;

[0027] Figure 5 It is the adsorption isotherm diagram of the zinc-based complex of the present invention for CO2, C2H2, C2H4 and C2H6 at 195K, the abscissa is the pressure, and the ordinate is the adsorption amount;

[0028] Figure 6 The adsorption isotherms of the zinc-based complex of the present invention for CO2, C2H2, C2H4 and C2H6 at 273K, the abscissa is the pressure, and the ordinate is the adsorption amount;

[0029] Figure 7 It is the adsorption isotherm diagram of CO2, C2H2, C2H4 and C2H6 of the zinc-based complex of the present invention at 298K, the abscissa is the pressure, and the ordinate is the adsorption amount;

[0030] Figure 8 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / C2H4 (v / v=1:99) at 195K, where the abscissa is time and the ordinate is relative concentration.

[0031] Fig. 9 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention for CO2 / C2H4 (v / v=10:90) at 195K, where the abscissa is time and the ordinate is relative concentration.

[0032] Fig.10 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / C2H4 / CO2 (v / v / v=1:98:1) at 195K, with the horizontal axis being time and the vertical axis being relative concentration.

[0033] Fig.11 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / C2H4 (v / v=1:99) at 298K, where the abscissa is time and the ordinate is relative concentration.

[0034] Fig.12 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / C2H4 (v / v=50:50) at 298K, where the abscissa is time and the ordinate is relative concentration.

[0035] Fig.13 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / CO2 (v / v=50:50) at 298K, where the abscissa is time and the ordinate is relative concentration.

[0036] Fig.14 This is a dynamic penetration experiment diagram of the zinc-based complex of the present invention to C2H2 / C2H4 / CO2 (v / v / v=1:98:1) at 298K, with the abscissa being time and the ordinate being relative concentration. DETAILED DESCRIPTION

[0037] The principles and features of the present invention are described in detail below in conjunction with implementation. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0038] Embodiment 1,

[0039] A method for preparing a zinc-based complex comprises the following steps:

[0040] A. Accurately weigh 0.0026 g, 0.0054 mmol, of 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 0.03 g, 0.11 mmol, of 4-(2,5-difluoro-4-bromophenyl)pyridine ligand, and 0.0189 g, 0.064 mmol, of zinc nitrate hexahydrate into a reaction container using an analytical balance. At room temperature, add 1 mL of a mixed solvent consisting of N,N-dimethylformamide, ethanol, and water into the reaction container, wherein the volume ratio of N,N-dimethylformamide, ethanol, and water is 5:2:1.

[0041] B. Place the mixed solution in step A in a glass bottle and keep it in a constant temperature blower at 90° C. for 48 hours to obtain a colorless, transparent, blocky zinc-based complex.

[0042] The obtained colorless and transparent crystalline zinc-based complex was tested at 293K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and the data was received on the EosCCD. A graphite monochromator was used, and λ(CuKα) was Data analysis was performed using the CrysAlisPro tool with a variable speed arbitrary angle scan mode from ω to 2θ, and absorption correction was performed. All structures were solved directly using the SHELXS program packaged in SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were treated anisotropically, and the hydrogen atoms of the organic ligands were generated by geometric symmetry (CH ). The crystal data shown in Table 1, the typical bond length data of the crystal shown in Table 2, and the typical bond angle data of the crystal shown in Table 3 are obtained. Table 1, Table 2 and Table 3 are as follows:

[0043] Table 1: Crystal data

[0044]

[0045]

[0046] Table 2: Typical bond length data of crystals (unit: )

[0047]

[0048]

[0049] Table 3: Typical bond angle data of crystals (unit: °)

[0050] O4 Zn1 O5 113.6(5) O4 Zn1 O9 115.1(5) O9 Zn1 O5 108.9(5) O1 Zn1 O4 112.2(6) O1 Zn1 O5 101.4(6) O1 Zn1 O9 104.5(6) N2 Zn2 O8 97.5(5) O7 Zn2 N2 107.9(5) O10 Zn2 N2 119.4(6) O10 Zn2 O7 125.7(6) O10 Zn2 O8 97.7(5)

[0051] like Figure 1 and Figure 2 As shown, the colorless and transparent crystalline zinc-based complex was tested at 293K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data was received on an EosCCD. A graphite monochromator was used, and λ(Cu Kα) was Data analysis was performed using the CrysAlisPro tool with a variable speed arbitrary angle scan mode from ω to 2θ, and absorption correction was performed. All structures were solved directly using the SHELXS program packaged in SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were treated anisotropically, and the hydrogen atoms of the organic ligands were generated by geometric symmetry (CH ). Combining the crystal data in Table 1, Table 2 and Table 3, the following relevant characterizations of the zinc-based complex are obtained:

[0052] The asymmetric unit consists of a quarter of the deprotonated ligand TMTA, a DPP ligand, a water molecule, a DMF molecule and three zinc ions.

[0053] The zinc ion is connected to four atoms in a four-coordinate mode. The four atoms connected to Zn1 are oxygen atoms (O2) from four carboxylates (O2-C1-O2) of three different ligands, and one is an oxygen atom (O1) from a water molecule; the four atoms connected to Zn2 are oxygen atoms (O2) from four carboxylates (O2-C1-O2) of three different ligands, and one is a nitrogen atom (N1) from the DPP ligand; the carboxylates (O2-C1-O2) in the ligand adopt a bidentate bridging mode to connect adjacent Zn ions, eventually forming a binuclear Zn3(TMTA)2(DPP)·DMF·H2O structure. Its unit cell parameters are the axial length Axis angle α = 60.225 (9) °, β = 73.437 (8) °, γ = 84.579 (7) °, the unit cell volume is Z=2.

[0054] The structure of the zinc-based complex of the present invention belongs to the triclinic system and the P-1 space group. The carboxyl groups in H3TMTA are all deprotonated and are connected to adjacent Zn ions by bidentate bridging. The Zn ions are bridged by carboxylic acid oxygen to form binuclear secondary structural units, and adjacent secondary structural units are connected by three carboxyl groups of the ligand.

[0055] like Figure 3 As shown, the colorless and transparent crystalline zinc-based complex was subjected to thermogravimetric analysis. The thermogravimetric test was conducted on a Mettler synchronous thermogravimetric analyzer, machine model RGA / DSC-1, with nitrogen as both the reaction gas and the protective gas, with a flow rate of 25 mL / min, a running time of 50 min, a heating rate of 10 °C / min, and a test temperature range of 40 to 900 °C. Figure 3 From the thermogravimetric curve, we can know that the zinc-based complex can be stable to about 433°C; the complex loses the coordinated solvent in the system at 200°C, the weight loss at 200-370°C is the partial decomposition of the ligand, and the zinc-based complex decomposes after 433°C. This shows that the zinc-based complex of the present invention has good stability and can be decomposed at high temperature.

[0056] like Figure 4 As shown, the colorless, transparent, crystalline zinc-based complex was detected by infrared spectroscopy. The infrared test was performed by KBr tablet method, and the 4000-400 cm -1 Infrared spectrum in the region. Figure 4 It can be seen that the complex is located at 3424cm -1The absorption peaks nearby can be attributed to the OH stretching vibration peak in water, which is located at 1660-1614 cm -1 and 1412~1380cm -1 The nearby absorption peaks can be attributed to the antisymmetric and symmetric stretching vibration peaks of carboxyl groups, respectively.

[0057] like Figure 5 , Figure 6 and Figure 7 As shown in the figure, the colorless and transparent crystalline zinc-based complex was tested by the ASAP 2020 instrument of the American Micromeritics Company. The zinc-based complex exhibited adsorption isotherms for low-carbon hydrocarbons composed of CO2, C2H2, C2H4 and C2H6 as shown in the figure. The adsorption amounts of CO2, C2H2, C2H4 and C2H6 at 195K were 235.84 cm 3 / g, 317.83cm 3 / g, 165.22cm 3 / g and 165.18cm 3 / g. The isotherm of the zinc-based complex for C2H2 shows a multi-step adsorption, which is a typical feature of the flexible pore structure. The isotherm reaches the first adsorption platform between 52KPa. When P>52kPa, the second step of adsorption occurs, and its maximum adsorption capacity reaches 317.83cm at 100kPa. 3 / g. The adsorption capacities of CO2, C2H2, C2H4 and C2H6 at 273K are 64.97 cm 3 / g, 100.23cm 3 / g, 101.92cm 3 / g and 96.2cm 3 / g, the adsorption capacities of CO2, C2H2, C2H4 and C2H6 at 298K are 42.5 cm 3 / g, 87.13cm 3 / g, 67.89cm 3 / g and 74.16cm 3 / g. Therefore, the differential adsorption amounts in the figure indicate that the zinc-based complex can be applied in the field of gas adsorption and separation.

[0058] like Figure 8-14As shown, the colorless transparent crystalline zinc-based complex is tested by a multi-component competitive adsorption penetration curve analyzer, the total flow rate of the mixed gas is 2mL / min, and the zinc-based complex exhibits separation effects on C2H2 / C2H4, C2H2 / CO2, C2H4 / CO2 and C2H2 / C2H4 / CO2 as shown in the figure. The separation times of C2H2 / C2H4 (v:v=1 / 99), CO2 / C2H4 (v:v=10 / 90), and C2H2 / C2H4 / CO2 (v:v:v=1 / 98 / 1) at 195K are 27.63min / g, 35.23min / g, and 37.39min / g, respectively. The separation times of C2H2 / C2H4 (v:v=1 / 99), C2H2 / C2H4 (v:v=50 / 50), C2H2 / CO2 (v:v=50 / 50) and C2H2 / C2H4 / CO2 (v:v:v=1 / 98 / 1) at 298K are 26.32 min / g, 22.89 min / g, 15.83 min / g and 4.77 min / g respectively.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A zinc-based complex, characterized in that: The general chemical formula is [Zn3(TMTA)2(DPP)·DMF·H2O], wherein Zn is a divalent zinc ion, TMTA is a deprotonated 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, and DPP is a 4-(2,5-difluoro-4-bromophenyl)pyridine ligand; The structure of the zinc-based complex belongs to the triclinic system, P-1 space group, and its unit cell parameters are the axial length Axis angle α=60.225(9)°, β=73.437(8)°, γ=84.579(7)°.

2. A method for preparing the zinc-based complex as claimed in claim 1, characterized in that: The steps include: A. Dissolve 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine ligand and zinc nitrate hexahydrate is 1:20:12.8, and the concentrations of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand and 4-(2,5-difluoro-4-bromophenyl)pyridine ligand in the solution are 0.0054 mmol / L and 0.064 mmol / L, respectively; B. Place the mixed solution in step A in a glass bottle and keep it at 90° C. for 24 to 48 hours to obtain the zinc-based complex.

3. The method for preparing the zinc-based complex according to claim 2, characterized in that: The solvent consists of N,N-dimethylformamide, ethanol and water, and the volume ratio of N,N-dimethylformamide, ethanol and water is 5:2:

1.

4. The method for preparing the zinc-based complex according to any one of claims 2 or 3, characterized in that: The molar ratio of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand, 4-(2,5-difluoro-4-bromophenyl)pyridine ligand and the zinc nitrate hexahydrate is 0.054:1.1:0.64, and the concentrations of the 4,4',4"-(2,4,6-trimethylbenzene-1,3,5)tribenzoic acid ligand and 4-(2,5-difluoro-4-bromophenyl)pyridine ligand in the solution are 0.0054 mmol / L and 0.064 mmol / L, respectively.

5. An application of the zinc-based complex as claimed in claim 1 in the field of light hydrocarbon gas separation, characterized in that: The zinc-based complex is tested for adsorption of low-carbon hydrocarbons consisting of CO2, C2H2, C2H4 and C2H6, and the differentiated adsorption amounts are obtained for adsorption separation.

Citation Information

Patent Citations

  • Nitrogen-oxygen mixed ligand zinc complex and preparation method thereof

    CN110330515A

  • Porous zinc-based MOF material with high thermal stability, and preparation method and application thereof

    CN113174054A

  • Thorium-based complex, preparation method and application of thorium-based complex in fluorescence detection and low-carbon hydrocarbon separation

    CN115947743A

  • Zinc-based metal organic framework material, preparation method thereof and application of zinc-based metal organic framework material in ethylene separation

    CN116082657A

  • Flexible zinc-based complex as well as preparation method and application thereof

    CN118084944A